Template-free synthesis of novel flower-like MnCo2O4 hollow microspheres for application in supercapacitors. Issue 2 (1st February 2016) - Che, Hongwei; Liu, Aifeng; Mu, Jingbo; Wu, Chunxia; Zhang, Xiaoliang
Abstract: Novel flower-like MnCo2 O4 hollow microspheres have been synthesized through a facile template-free solvothermal method combined with calcination. The as-synthesized flower-like MnCo2 O4 hollow microspheres have a diameter of 3.0 μm, and constructed by numerous loosely arraying nanoflakes with a thickness of 20 nm. Based on their unique flower-like and hollow structures, these flower-like MnCo2 O4 hollow microspheres display a good capacitive behavior with a specific capacitance of 235.7 F g −1 at a current density of 1.0 A g −1 and a good specific capacitance retention of 93.6% after 2000 continuous charge–discharge cycles. The excellent capacitive properties and stability suggest that these flower-like MnCo2 O4 hollow microspheres could be promising electroactive materials for supercapacitors.